Direct real-time RT-PCR for the detection of dengue virus from patient serum in Lao PDR. - Vilayouth Phimolsannousith; Malavanh Vongsouvath; Padthana Kiedsathid; Manivanh Vongsouvath; Elizabeth A Ashley; Audrey Dubot-Pérès (PLoS ONE)
Introduction Dengue fever is a growing global concern with an estimated 100-400 million infections every year and rising mortality over the past decade. In 2017, 40,000 deaths were attributed to dengue. Real-time reverse transcription PCR (RT-qPCR) is the gold standard technique to detect dengue virus (DENV) during the acute phase of the infection. However, it requires prior RNA purification which is costly and time consuming. We evaluated direct RT-qPCR using Luna Universal Probe One-Step RT-qPCR kit (Luna RT-qPCR) for the detection of DENV in sera. Methods Luna RT-qPCR conditions were optimized using DENV2 isolates. The efficiency of direct Luna RT-qPCR was evaluated on a panel of 132 patient sera using RNA purification (EZ1&2 Virus Mini Kit) followed by RT-qPCR (SuperScript III Platinum One-Step qRT-PCR system) as reference standard. Results The sensitivity (95% CI) of direct Luna RT-qPCR using neat patient sera was 34% (25-45). By reducing PCR inhibitors through a 1/10 dilution of the sera, the sensitivity improved to 86% (95% CI: 77-92). Comparable results were obtained between direct Luna RT-qPCR and reference standard process for samples with Cq < 35. Conclusion The results obtained in this study are promising. Direct RT-qPCR for DENV detection in patient sera, could make PCR-based dengue detection and typing, and potentially other target detections, more affordable for reference laboratories in LMICs by reducing reagent cost by approximately two-thirds. Further studies are needed to evaluate DENV direct RT-qPCR on prospective samples in diagnosis context and to improve the sensitivity by minimizing the impact of inhibitors.